2009
DOI: 10.1088/0004-637x/692/2/1287
|View full text |Cite
|
Sign up to set email alerts
|

DETECTIONS OF LYMAN CONTINUUM FROM STAR-FORMING GALAXIES ATz∼ 3 THROUGH SUBARU/SUPRIME-CAM NARROW-BAND IMAGING

Abstract: Knowing the amount of ionizing photons from young star-forming galaxies is of particular importance to understanding the reionization process. Here we report initial results of Subaru/Suprime-Cam deep imaging observation of the SSA22 proto-cluster region at z = 3.09, using a special narrow-band filter to optimally trace ionizing radiation from galaxies at z ∼ 3. The unique wide field-of-view of Suprime-Cam enabled us to search for ionizing photons from 198 galaxies (73 Lyman break galaxies (LBGs) and 125 Ly-α … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
332
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(363 citation statements)
references
References 33 publications
29
332
2
Order By: Relevance
“…Despite these caveats we note that our calculated escape fractions are broadly consistent with those estimated for star-forming galaxies at z ≈ 3 (e.g. Iwata et al 2009;Siana et al 2015).…”
Section: Star Formation Associated With Lyman-alpha Blobssupporting
confidence: 86%
“…Despite these caveats we note that our calculated escape fractions are broadly consistent with those estimated for star-forming galaxies at z ≈ 3 (e.g. Iwata et al 2009;Siana et al 2015).…”
Section: Star Formation Associated With Lyman-alpha Blobssupporting
confidence: 86%
“…In previous articles where z ∼ 3 galaxies were imaged in the LyC, it was shown that emitted ionizing photons can be found at some distance from the center of the galaxies (Iwata et al 2009;Nestor et al 2011). While there is no possible way of acquiring LyC images of Haro 11, we do know that this local galaxy has star-forming regions out to, and beyond, the 30 × 30 LWRS aperture of FUSE.…”
Section: Discussionmentioning
confidence: 99%
“…Iwata et al (2009) and Nestor et al (2011) demonstrated that LyC leakage can be found spatially off-set from the main body of the non-ionizing UV continuum (although some of these detections statistically are likely to be lower redshift contaminants). To estimate the distance from the center at which we would expect most of the ionizing radiation to slip through a picket fence structure in Haro 11, we adopt a simple model with two components -the ionizing stars and the neutral gas.…”
Section: Haro 11mentioning
confidence: 99%
See 1 more Smart Citation
“…We allow fesc to vary between 0.01 and 1. Observations of star-forming galaxies at z ∼ 1-3 suggest a small average ionizing escape fraction from a few percent to smaller than 15%, which is likely to increase towards fainter galaxies (or equivalently towards higher redshifts, e.g., Iwata et al 2009;Siana et al 2010;Nestor et al 2013;Mostardi et al 2015). In recognition of the redshift dependence of Mmin, we model its variation by rescaling Mmin(z) as given by Okamoto et al (2008) by a factor of 0.1-10.…”
Section: Joint Analysis Of Galaxy Populations and The Reionization Obmentioning
confidence: 99%